Indonesian English Teachers’ Multicultural Awareness : A Case Study at Two Pesantren-Based Schools - Chubbi Millatina Rokhuma; Rayinda Eva Rahmah; Milatil Azka; Nabila Attar Tsania (PANYONARA: Journal of English Education, 2023)
Multicultural awareness is one of pivotal things for English teachers. English teachers who teach a language linking people around the world with many differences, should have a good understanding of multicultural awareness so that they can be an excellent example for the students of how to behave well to people with different cultural background. The aim of this study is to describe Indonesian English teachers’ multicultural awareness in teaching multicultural students and explore the influencing factors of English teachers’ multicultural awareness in teaching multicultural students. This study was conducted using a qualitative approach. The data were collected through interviewing the English teachers and some students having different multicultural background as well as observing the English learning process. The gathered data were analysed using steps of Miles and Huberman. The research result shows that the English teachers of the two pesantren-based schools have good multicultural awareness by showing good cultural empathy, open-mindedness, emotional stability, social initiatives, flexibility, and self-efficacy toward multiculturalism. This condition is encouraged by the teachers’ knowledge about multiculturalism and the school leaders supporting solid relationships among the cultural differences. The result of this study is supposed to be able to build English teachers’ awareness of how to show multicultural attitudes at school.